Reconstructive facial plastic surgery a problem-solving manual - Weerda, Hilko (Thieme, 2015)
Drawing on decades of operating room and teaching experience, Dr. Weerda and his team offer a complete guide to reconstructive options for facial, head, and neck defects in this eagerly awaited second edition. Their systematic, step-by-step approach, with an emphasis on meticulous preoperative planning, evaluation of alternatives, and selection of the best procedure, ensures optimal results for all patients. Focusing on the questions, problems, and technical solutions most commonly encountered in everyday practice, this compact book will be valuable to both the novice and more experienced